COORDINATION OF RIAU NATURAL RESOURCES CONSERVATION CENTER AND TRADITIONAL INSTITUTIONS IN PRESERVING LOCAL WISDOM OF BULUH CINA VILLAGE NATURAL TOURISM PARK 2017-2018 - Ramlan Darmansyah; Raja Muhammad Amin (Kybernan: Jurnal Studi Kepemerintahan, 2021)
This research aims to see the coordination between the Riau Natural Resources Conservation Center and Traditional Institutions in the implementation of the local wisdom preservation program in Buluh Cina Village Nature Tourism Park. Before becoming the Natural Tourism Park of Buluh Cina Village, the Kenegerian Rimbo Tujuh Traditional Forest was a local wisdom for the People of Buluh Cina Village. The customary forest is preserved and protected by the Traditional Institution, the Village Government and the Chinese Buluh Village Community. After changing its function to a Nature Tourism Park, it was then managed by the Riau Natural Resources Conservation Center. The method in this research is a qualitative approach, which describes the data in the form of a narrative. As for the data sources in this study, namely interviews and documentation. The results of this research are that the coordination between the Riau Natural Resources Conservation Center and the Traditional Institutions in the implementation of the local wisdom preservation program in Buluh Cina Village Nature Park in 2017-2018 is still not going well, it can be seen from the implementation of the Nature Tourism Park preservation program which still does not involve Traditional Institutions and the Village Government. As for the inhibiting factors, namely the domination of intervention from the Riau Natural Resources Conservation Agency, the absence of special arrangements related to coordination and cooperation, the absence of financial resources in the implementation of the Buluh Cina Village Nature Tourism Park management program and the lack of communication links between the Center for Natural Resources Conservation and Traditional Institutions.